Laboratory Diagnosis of Syphilis: A Survey to Examine the Range of Tests Used in Canada. Issue 3 (2011) - Tsang, Raymond SW.; Radons, Sandra Michelle; Morshed, Muhammad; on behalf of the Syphilis Laboratory Task Group of the Canadian Public Health Laboratory Network,
Abstract : Laboratory diagnosis of syphilis has undergone major changes in the past decade with the introduction of immunoassays and recombinant Treponema pallidum antigens as screening tools for syphilis infection. To address this change in laboratory practice, a national syphilis laboratory working group was established with members from the Public Health Agency of Canada, provincial public health laboratories across the country as well as sexually transmitted infection researchers, clinicians and epidemiologists. This working group aims to examine how the use of newer immunoassays will affect syphilis diagnosis, surveillance and disease management. To provide a baseline for this work, an e-mail survey was conducted in the fall of 2009 to determine current laboratory practices for syphilis diagnosis in Canada. The most commonly used tests were rapid plasma reagin, enzyme immunoassay, T pallidum passive particle agglutination, venereal disease research laboratory, fluorescent treponemal antibody absorption, line immunoassay and polymerase chain reaction with 92%, 36%, 32%, 20%, 12%, 12% and 12% of the responding laboratories reporting using these tests, respectively. The ultimate goal of this working group will be to update laboratory guidelines for the diagnosis of syphilis, and to identify syphilis surveillance and research priorities in Canada.